Analisis Strategi Pemasaran PT. Bank Sumut Kantor Cabang Pembantu Syariah Rantau Prapat dalam Meningkatkan Jumlah Nasabah Pembiayaan Multiguna - Ledis Izzah Harahap (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This study discusses the marketing strategy of PT. Bank Sumut Kantor Cabang Pembantu Syariah Rantau Prapat in increasing the number of multi-purpose financing customers. The bank utilizes product, price, promotion, and distribution strategies to attract customers. The research method used is qualitative with a descriptive approach. The results show that the bank uses sales promotion, personal selling, and advertising to increase the number of customers. The marketing strategy of Bank Syariah includes product, price, promotion, and distribution strategies. PT. Bank Sumut Kantor Cabang Pembantu Syariah Rantau Prapat uses sales promotion, personal selling, and advertising to increase the number of multi-purpose financing customers. This includes distributing brochures, personal selling by employees, placing banners, and creating company magazines. All information is also posted on the official website and social media